Interaction of ACP and MDP and its effect on dentin bonding performance. (March 2019) - Zhang, Ling; Wang, Wenting; Wang, Chaoyang; Li, Mingxing; Wang, Zhe; Su, Zhiwei; Fu, Baiping
Abstract: Objectives: The study investigated the solid reactants of amorphous calcium phosphate (ACP) nanoparticles with 10-methacryloyloxydecyl dihydrogen phosphate (MDP) in ethanol-aqueous solution, and the effect of ACP-MDP suspension as a novel primer on dentin micro-tesnisl bond strengths (MTBS) prior to application of self-etch adhesives. Materials and methods: The ACP nanoparticles were synthesized. The solid reactants of ACP nanoparticles with MDP ethanol-aqueous solution were analyzed by TEM, SEM, XRD and AFM. After the ACP-MDP complexes were attacked by alkaline, acidic and self-etch adhesive challenges, they were analyzed with TEM. The polished mid-coronal dentin surfaces of six third molars were treated with ACP-MDP suspension, 5% MDP solution or not (served as control), and thoroughly water-sprayed. The pretreated dentin surfaces were applied with a self-etch adhesive (Clearfil S3 Bond) and placed with a composite resin (Clearfil Majesty). After 24 h, the resin-bonded samples were cut into multiple beams before the MTBS tests were performed. The failure modes were determined by a stereo-microscopy. The pretreated dentin surfaces were analyzed by SEM. The resin-dentin interfaces were analyzed with TEM. Results: The ACP nanoparticles in the MDP ethanol-aqueous solution at certain molar ratio of Ca:MDP (0.12:1) could self-assemble into ACP-MDP complexes consisting of nanolayering structures. The ACP-MDP self-assembly went from ACP nanoparticles, beaded structures, and twig-like structures to networks. The ACP-MDP complexes can be resistant to adhesive challenge, but not to alkaline and acidic challenges. ACP-MDP complexes possessed a similar modulus of elasticity to dentin, and were stable at least for 3 months. Furthermore, the dentin surfaces treated with ACP-MDP suspension could significantly increase the dentin MTBS when compared with control and those treated with 5% MDP solution ( P < 0.05). Conclusion: The ACP-MDP suspension at certain molar ratio of Ca:MDP (0.12:1) could be self-assembled into ACP-MDP complexes consisting of nanolayering structures, and could be used as a novel primer to greatly improve the dentin bond strengths.